ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) AND FIRM VALUE: EVIDENCE FROM NON-FINANCIAL COMPANIES IN INDONESIA: - Samuel Sitinjak; Fida Muthia; Kemas M. Husni Thamrin (Universitas Airlangga, 2025)
This study aims to empirically examine the impact of Environmental, Social, and Governance (ESG) on firm value in Indonesia. ESG Score published by refinitiv workspace is used as independent variable, while firm value is measured using Tobins’Q. Profitability, firm size and industry sector are used asa control variables in this study. 59 non-financial companies in Indonesia from 2017 to 2022 are used as the sample of this study. The data is analysed using Random Effect Model (REM). The results of the study indicate that Environmental, Social, and Governance (ESG) has a significant positive impact on firm value (Tobin's Q). Additionally, the control variable Return on Assets (ROA) also shows a significant positive effect on firm value, whereas company size (SIZE) demonstrates a significant negative impact on firm value. This gives implication that sustainable information may be perceived as a positive signal for investors.